2007
DOI: 10.1080/15321810701209704
|View full text |Cite
|
Sign up to set email alerts
|

Clearing of Suspensions ofMicrococcus lysodeikticusCatalysed by Lysozymes from Hen, Goose, and Turkey Egg Whites, Human Milk, and Phage T4. Assessment of Potential as Signal Generators for Homogeneous Enzyme Immunoassays for Urinary Steroids

Abstract: Lysozymes (3.2.1.17) from goose (Anser anser) egg white, turkey (Melagris gallopavo) egg white, phage T4 and human milk were compared with hen egg white lysozyme in their ability to clear a suspension of Micrococcus lysodeikticus. All of the lysozymes, except hen egg white lysozyme, catalysed the clearing of the Micrococcus lysodeikticus suspension in a biphasic fashion. Compared to hen egg white lysozyme, the total absorbance or transmission change over 5 and 20 minutes was less in all cases, except for human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…LYSO breaks bacterial cell walls made of peptidoglycan via hydrolysis of the β (1–4) glucosidic bond between N-acetylmuramic acid and N-acetylglucosamine [28, 29]. M. lysoleikticus possesses a peptidoglycan wall [30]. Our results showed that baicalin enhanced the activity of LYSO in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 88%
“…LYSO breaks bacterial cell walls made of peptidoglycan via hydrolysis of the β (1–4) glucosidic bond between N-acetylmuramic acid and N-acetylglucosamine [28, 29]. M. lysoleikticus possesses a peptidoglycan wall [30]. Our results showed that baicalin enhanced the activity of LYSO in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 88%